Anti-Infective Drugs during Continuous Hemodialysis –Using the Bench to Learn What to do at the Bedside. Issue 1 (January 2015) - Roehr, Anka C.; Frey, Otto R.; Koeberer, Andreas; Fuchs, Thomas; Roberts, Jason A.; Brinkmann, Alexander
Purpose: The main objective of this study was to investigate the clearance of 11 selected anti-infectives in an in vitro model of continuous veno-venous hemodialysis (CVVHD), in order to suggest rational dosing strategies for clinical practice. Methods: Ceftazidime, ciprofloxacin, flucloxacillin, gentamicin, linezolid, meropenem, metronidazole, piperacillin, rifampicin, vancomycin and voriconazole were studied in two different solvents (sodium chloride 0.9% and HSA 5%) using a multifiltrate dialysis device by Fresenius Medical Care (Bad Homburg, Germany). For each solution, prefilter, postfilter, and dialysate samples were drawn simultaneously during one hour of dialysis and were assayed. Results: The clearance of all drugs except rifampicin in sodium chloride 0.9% was comparable (mean 1.76 ± 0.11 l/h). The clearance of these agents in human serum albumin solution 5% was reduced by between 5.3% and 72.2%. The unbound drug fraction correlated with a lower clearance in HSA 5% (Pearson correlation coefficient r = 0.933; p = 0.00008). No correlation between clearance in HSA 5% and the drugs' molecular weight was found (Pearson correlation coefficient r = 0.388; p = 0.268). Rifampicin was detected to bind to the surface of the polysulfone filter used. Dialysis clearance of ceftazidime, gentamicin, linezolid, meropenem, metronidazole, piperacillin and vancomycin during CVVHD accounted for over 25% of the total body clearance of population pharmacokinetic data for renally impaired patients. Conclusions: The results from this study highlight that dose adaptations are needed for most of the drugs under investigation for patients undergoing CVVHD. In combination with polysulfone filters, rifampicin should be used with care in this setting.